Better the devil you know: The Influence of Political Incumbency on Australian Financial Market Uncertainty - Smales, Lee (J A I Press Inc., 2015)
The Australian federal election cycle, which occurs approximately every 3 years, causes much media attention and invokes indecision regarding investment decisions in both the real economy and financial markets. This paper constructs measures of political uncertainty and formally explores their relationship with market uncertainty, as measured by implied volatility. The empirical evidence suggests that increasing (decreasing) levels of uncertainty around the election result induce higher (lower) levels of market uncertainty. In a case of the market preferring the devil it knows, an increasing (decreasing) likelihood of the incumbent party, whose economic policies are well-known, winning the election, reduces market uncertainty. The results remain significant even after con-trolling for a number of macroeconomic variables, and when an alternative GARCH framework is considered.